Síntese e avaliação biológica de intermediários sintéticos de derivados pirazolidínicos e iIsoxazolidínicos - (:unkn) unknown (Universidade Estadual de Goiás, 2011)
The discovery of new chemical entities will drugs candidates starts with the basic research of a new compound bioativo, this process to be effective it needs to be well articulated. Based on the search for bioactive substances isolated from natural sources and highlight the veraguesin 1 and grandisin 2 compounds, which showed potent trypanocidal activity. With the prototype compounds was proposed and the synthesis of analogues, such as derivatives pirazolidínes 5 and isoxazolidines 6 with different modifications to produce new bioactive compounds. To this end we propose the use of compounds of the class of chalcones as precursors for the synthesis of compounds 5 and 6. In this work we synthesized and evaluated the cytotoxic activity of a series of chalcones due to structural similarity with natural compounds combrestastatinas. In this study 46 chalcones were synthesized, and by the method MTT conducted screening of cytotoxic activity of these substances to determine the antitumor potential in the face of strains of human cancer MDAMB-435, (human melanoma), HCT-8 (colon-human) and SF-295 (Nervous system – human), 36 chalcones showed significant cytotoxic potential. The promising chemical and biological results reported here enable the use on the class of chalcones in the representation of new therapeutic possibilities.
Synthesis and biological evaluation of intermediate and synthetic derivatives pirazolidinic and isoxazolidinic
Keywords: Chalconas; Atividade antitumoral; Bioatividade; Chalcones; Antitumor activity; Bioactivity; CIENCIAS EXATAS E DA TERRA::QUIMICA; QUIMICA::FISICO-QUIMICA